A close examination of BCRP's role in lactation and methods for predicting drug distribution into milk - Caroline Sychterz; Hong Shen; Yueping Zhang; Michael Sinz; Amin Rostami‐Hodjegan; Brian J. Schmidt; Lu Gaohua; Aleksandra Galetin (CPT: Pharmacometrics & Systems Pharmacology)
Abstract Breastfeeding is the most complete nutritional method of feeding infants, but several impediments affect the decision to breastfeed, including questions of drug safety for medications needed during lactation. Despite recent FDA guidance, few labels provide clear dosing advice during lactation. Physiologically based pharmacokinetic modeling (PBPK) is well suited to mechanistically explore pharmacokinetics and dosing paradigms to fill gaps in the absence of extensive clinical studies and complement existing real‐world data. For lactation‐focused PBPK (Lact‐PBPK) models, information on system parameters (e.g., expression of drug transporters in mammary epithelial cells) is sparse. The breast cancer resistance protein (BCRP) is expressed on the apical side of mammary epithelial cells where it actively transports drugs/substrates into milk (reported milk: plasma ratios range from 2 to 20). A critical review of BCRP and its role in lactation was conducted. Longitudinal changes in BCRP mRNA expression have been identified in women with a maximum reached around 5 months postpartum. Limited data are available on the ontogeny of BCRP in infant intestine; however, data indicate lower BCRP abundance in infants compared to adults. Current status of incorporation of drug transporter information in Lact‐PBPK models to predict active secretion of drugs into breast milk and consequential exposure of breast‐fed infants is discussed. In addition, this review highlights novel clinical tools for evaluation of BCRP activity, namely a potential non‐invasive BCRP biomarker (riboflavin) and liquid biopsy that could be used to quantitatively elucidate the role of this transporter without the need for administration of drugs and to inform Lact‐PBPK models.